Advancing global health equity: the transformative potential of community-based surveillance in developing countries - Izquierdo Condoy, Juan S. (2023)
In community settings, medical surveillance is an effective strategy for infectious disease control. It involves systematic epidemiological surveillance, facilitating the collection, analysis, and dissemination of health data. This process is vital for mitigating outbreak impacts and managing disease spread. The development and administration of public health programs within these frameworks are key to enhancing preparedness for future outbreaks, a necessity in the context of continual health threats (1). Although surveillance strategies have classically relied predominantly on data from institutional sources like hospitals and public records, the reach of such methods has been shown to be limited, particularly in low- and middle-income countries. Such limitations stem from factors like inadequate healthcare infrastructure, cultural practices in rural areas, and incomplete civil registration systems (2–4). Addressing these challenges, community-based surveillance, a well-established and historically significant tool in health systems, has seen a broadening of its scope. Initially focused on infectious diseases, this method of surveillance has expanded its applicability to encompass a diverse range of healthcare contexts (5–9). Reflecting on its conceptual evolution over decades, as detailed by Rojanaworarit (10), community-based surveillance now plays a crucial role in monitoring and responding to various health events, from disease outbreaks to environmental hazards, thereby shaping public health actions and policies. Notably, during health crises like pandemics, community-based systems have been found to be remarkably effective, sometimes surpassing formal healthcare systems in their efficacy (9)